Particle characterization in an urban synthetic turf: insights into turf and vehicular wear - Perla E. Medina-Corral; Francisco R. Berrellez-Reyes; Diana M. Meza-Figueroa; Benedetto Schiavo; Belem Gonzalez-Grijalva; Aracely Angulo-Molina (Environmental Geochemistry and Health, 2026)

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Hollow Heart Incidence in Potato Farms from the Tropical Volcanic Highlands: Assessing the Effect of Ca Fertilizer Additions - José Mario Jiménez-Calvo; Manuel E. Camacho-Umaña; Arturo Brenes Angulo (Potato Research, 2026)

Integrative diagnostic and pathophysiological characterization of canine Chagas disease using sCha peptide and Trypanosoma cruzi lysate antigens - L. Vega; R. Lazo; P. Miranda; E. Naranjo; H.J. Carrasco; N. Girones; M. Fresno; M. Yajure; H. Rodríguez-Angulo (Veterinary Parasitology, 2026)

Morphology and particle size distribution in the indoor dust: A hidden threat to human health? - D. Meza-Figueroa; E. Vega; J. Entwistle; A. Angulo-Molina; A. Valencia-Meza; B. Schiavo; V. Rodriguez; B. González-Grijalva; F. Berrellez-Reyes; C. Ortega-Rosas; A. Wellens; A. Namdeo (Environmental Geochemistry and Health, 2026)

Distributed optical fibre sensing in physical oceanography: emergence and future prospects - Alberto C. Naveira Garabato; Carl P. Spingys; Andrew J. Lucas; Tiago S. Dotto; Christian T. Wild; Scott W. Tyler; Ted A. Scambos; Christopher B. Kratt; Giuseppe Cappelli; Ethan F. Williams; Mariona Claret; Hannah E. Glover; et al. (Ocean Science, 2026)
Distributed optical fibre sensing (DOFS) is a technology that enables continuous, real-time measurements of a range of environmental parameters along the length of a fibre optic cable. In this article, we review the recently emerged applications of DOFS techniques in physical oceanography and offer a perspective on the technology's potential for future growth within the field. The introduction of DOFS to physical oceanography is contextualised with a brief history of the technology, which spun off primarily from the use of seafloor-laid optical fibres for telecommunications purposes. The key components and underpinning physics of a DOFS system are outlined and, on their basis, the suite of variables that are observable with DOFS are discussed. The implementation factors of DOFS, which include trade-offs between measurement accuracy and spatio-temporal resolutions and ranges, are also examined. The physical oceanographic applications of DOFS to date are then illustrated with case examples of four distinct DOFS techniques: distributed temperature sensing (DTS), which can provide ocean temperature observations; distributed static strain sensing (DSS) and distributed acoustic sensing (DAS), which are sensitive to temperature, cable strain and strain-associated variables, such as pressure and ocean velocity; and ultra-long-range observations of ocean currents with optical interferometry. The forthcoming prospects of DOFS in physical oceanography are considered, and are proposed to include new fibre optic-based approaches to sense ocean salinity and measure through the water column. We conclude with reflections on the future role of DOFS within the Global Ocean Observing System, and highlight the opportunities provided by the existing world-wide network of seafloor-laid optical fibres.

Grafting surgery elicits systemic changes in antioxidant and immune responses in red abalone (Haliotis rufescens) - Alejandro Rojas-Figueroa; Carlos Angulo; Andrés Granados-Amores; Gabriel Correa-Reyes; Pedro E. Saucedo (Aquaculture, 2026)

Characterization of the microbial community in the rhizosphere of wheat genotypes from a reference mapping population (ITMI-b) at three stages of development - Cristina Escobedo-Fregoso; María Casandra Sánchez Angulo; Ángel E. Carrillo-García; María G. Caamal-Chan; Reyna De Jesús Romero-Geraldo; Fausto Valenzuela-Quiñonez; Abraham Loera-Muro (Plant and Soil, 2026)

Assessing Prokaryotic Benthic Communities in the Red Sea - Christopher A. Hempel; Larissa Frühe; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Diego E. Rivera Rosas; Amal A. Bajaffer; Wajitha J. R. M. Sait; Alexandra Steckbauer; Taiba Alamoudi; Jacqueline V. Alva García; Shannon G. Klein; et al. (Environmental Microbiology, 2026)
Marine sediments host diverse benthic prokaryotic communities that are integral to global biogeochemical cycles. However, the spatial distribution and environmental drivers of these communities, particularly in unique environments like the Red Sea, remain largely underexplored. In this study, we examine benthic prokaryotic communities sampled during the Red Sea Decade Expedition (RSDE) using 16S rRNA gene sequencing across five major regions along the Red Sea's latitudinal gradient and three depth strata. Our findings reveal distinct biogeographical patterns shaped by depth, latitude, and oxygen availability, with clear shifts in microbial community composition across the epibenthic, mesobenthic and bathybenthic zones. Bathybenthic communities exhibited consistently low levels of OTU richness throughout the Red Sea, likely due to uniform niche environmental conditions at depth, while shallower communities showed higher OTU richness towards the Southern Red Sea. The southern region harboured higher relative abundances of Chloroflexi and reduced relative abundances of Proteobacteria and Acidobacteriota relative to the northern regions. Extreme environments, such as the Atlantis II brine pool, supported specialised microbial communities likely adapted to extreme conditions like hypersalinity. This study established a critical baseline for understanding the responses of marine microbial communities to climate change and their roles in biogeochemical processes.

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

Description of an Enterococcus faecium genotype vanB outbreak in a hospitalization ward - M. Andrés; A. Fajardo; M. C. García; L. Grau; Y. Angulo; V. Marín; V. Plasencia; G. Santillana; E. Jiménez; M. Ballestero (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Particle‐Associated Bacterioplankton Communities Across the Red Sea - Larissa Frühe; Shannon G. Klein; Carlos Angulo‐Preckler; Anastasiia Martynova; Taiba Alamoudi; Jacqueline V. Alva García; Silvia Arossa; Jessica Breavington; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Anieka J. Parry; et al. (Environmental Microbiology, 2025)
Pelagic particle‐associated bacterioplankton play crucial roles in marine ecosystems, influencing biogeochemical cycling and ecosystem functioning. However, their diversity, composition, and dynamics remain poorly understood, particularly in unique environments such as the Red Sea. In this study, we employed eDNA metabarcoding to comprehensively characterise bacterioplankton communities associated with pelagic particles in a three‐dimensional assessment spanning depths from the surface to a depth of 2300 m along the full length of the eastern Red Sea within the exclusive economic zone of the Kingdom of Saudi Arabia. Our results reveal a diverse assemblage of taxa, with Pseudomonadota, Cyanobacteriota, and Planctomycetota being the dominant phyla. We identified pronounced spatial variability in community composition among five major Red Sea geographical regions, with a third of all amplicon sequence variants being unique to the Southern Red Sea in contrast to a relatively homogenous distribution along the water column depth gradient. Our findings contribute to a deeper understanding of microbial ecology in the Red Sea and provide valuable insights into the factors governing pelagic particle‐associated bacterioplankton communities in this basin.

Antifungal effect of Bonellia flammea extracts against Colletotrichum magnum in postharvest fruits of Carica papaya cv. Maradol - E. Herrera-Parra; J. Cristóbal-Alejo; A. Magaña-Alvarez; I. L. Medina-Baizabal; Marcela Gamboa-Angulo (Journal of Plant Diseases and Protection, 2024)

Biogenic Ag2O nanoparticles with “Hoja Santa” (Piper auritum) extract: characterization and biological capabilities - Dalia S. Aguilar-Ávila; M. Reyes-Becerril; Carlos A. Velázquez-Carriles; Gabriela Hinojosa-Ventura; María E. Macías-Rodríguez; Carlos Angulo; Jorge M. Silva-Jara (BioMetals, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Comparison of the blood biochemical values of foraging and nesting Olive Ridley turtles (Lepidochelys olivacea) from Sinaloa, Mexico - Jorge Valdés-Flores; César P. Ley-Quiñonez; Nidia León-Sicairos; Hector Flores-Villaseñor; Jorge Velázquez-Román; Uriel Angulo-Zamudio; Alan Zavala-Norzagaray; Catherine E. Hart; Vicente Olimón-Andalón; Renato Leal-Moreno; Ingmar Sosa-Cornejo; A. Alonso Aguirre; et al. (Marine Environmental Research, 2024)

Mangrove development on a remote volcanic island in the South Atlantic - José Tasso Felix Guimarães; Gabriel Negreiros Salomão; Prafulla Kumar Sahoo; Márcio Sousa da Silva; Wilson Nascimento Júnior; Pedro Walfir Martins e Souza Neto; Hortencia Maria Barbosa de Assis; Luiza Santos Reis; Ana Maria Góes; Paulo César Giannini; Rodolfo José Angulo; Marcelo Rollnic; et al. (Marine Geology, 2024)

Comparative phylogeography and demographic histories of five widely distributed tropical eastern Pacific fishes - Paola N. Palmerín-Serrano; Victor J. Piñeros; D. Ross Robertson; Arturo Angulo; Eduardo Espinoza; Enrique Barraza; Juan E. Martínez-Gómez; María G. Solís-Gúzman; Nancy Calderón-Cortés; Jonathan Valdiviezo-Rivera; Omar Domínguez-Domínguez (Marine Biology, 2023)

Highly Pathogenic Avian Influenza (HPAI) strongly impacts wild birds in Peru - Víctor Gamarra-Toledo; Pablo I. Plaza; Fernando Angulo; Roberto Gutiérrez; Oscar García-Tello; Patricia Saravia-Guevara; Fernando Mejía-Vargas; Mirbel Epiquién-Rivera; Gonzalo Quiroz-Jiménez; Paola Martinez; Deyvis Huamán-Mendoza; Giancarlo Inga-Díaz; et al. (Biological Conservation, 2023)

Comparative analysis of anesthetic agents used in pre-operative therapy for pearl culture in the red abalone Haliotis rufescens (Swainson, 1822) - Alejandro Rojas-Figueroa; Carlos Angulo; Rubén Araya; Andrés Granados-Amores; Francisco A. Guardiola; Pedro E. Saucedo (Aquaculture, 2023)

Reproductive performance of hair ewes and rams implanted with melatonin previous to the anestrus season in northwest Mexico - José C. Leyva-Corona; Norberto I. Angulo-Valenzuela; Blanca M. Laborin-Escalante; Miguel A. Gastelum-Delgado; N. Jahzeel Silva-Avila; Pablo Luna-Nevárez; Carlos E. Aragón-López; Miguel A. Sánchez-Castro; Marcela I. Morales-Pablos (Tropical Animal Health and Production, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Ecological niches, endemism and conservation of the species in Selenicereus (Hylocereeae, Cactaceae) - Brandon E. Gutiérrez-Rodríguez; Roger Guevara; Diego F. Angulo; Catalina Ruiz-Domínguez; Victoria Sosa (Brazilian Journal of Botany, 2022)

Postharvest application of partitioned plant extracts from Sinaloa, Mexico for controlling papaya pathogenic fungus Colletotrichum gloeosporioides - Jordi G. López-Velázquez; Francisco Delgado-Vargas; Lidia E. Ayón-Reyna; Gabriela López-Angulo; Silvia Bautista-Baños; Yesenia G. Uriarte-Gastelum; Martha E. López-López; Misael O. Vega-García (Journal of Plant Pathology, 2021)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Hereditary Ataxias in Cuba: A Nationwide Epidemiological and Clinical Study in 1001 Patients - Luis Velázquez-Pérez; Jacqueline Medrano-Montero; Roberto Rodríguez-Labrada; Nalia Canales-Ochoa; Jandy Campins Alí; Frank J Carrillo Rodes; Tania Rodríguez Graña; María O. Hernández Oliver; Raul Aguilera Rodríguez; Yennis Domínguez Barrios; Reydenis Torres Vega; Lissi Flores Angulo; et al. (The Cerebellum, 2020)

Quantile-based spatiotemporal risk assessment of exceedances - J. L. Romero; A. E. Madrid; J. M. Angulo (Stochastic Environmental Research and Risk Assessment, 2018)

High-carotenoid maize: development of plant biotechnology prototypes for human and animal health and nutrition - C. Zhu; G. Farré; D. Zanga; J. Lloveras; A. Michelena; J. P. Ferrio; J. Voltas; G. Slafer; R. Savin; R. Albajes; M. Eizaguirre; C. Lopez; et al. (Phytochemistry Reviews, 2018)

In vivo and in vitro studies using larval and adult antigens from Neobenedenia melleni on immune response in yellowtail ( Seriola lalandi ) - M Reyes‐Becerril; E Alamillo; A Trasviña; I Hirono; H Kondo; W Jirapongpairoj; F Ascencio‐Valle; C Angulo (Journal of Fish Diseases, 2017)
Neobenedenia melleni is a monogenean parasite that causes significant mortality and economic losses in fish aquaculture. Changes in the antigenic composition of this parasite occur during its developmental stages. In this study, we evaluated humoral parameters in serum and transcriptional immune responses of yellowtail naturally infected with N. melleni . In addition, in vitro assays were performed to study the stimulatory effects of antigens from larvae and adults on spleen leucocytes from non‐infected fish at 6 and 24 h post‐stimulation. The results showed enhanced total protein, myeloperoxidase and antiprotease activities in N. melleni ‐infected fish compared with non‐infected ones. The induction of Toll‐like receptors (TLRs) and pro‐inflammatory cytokines in spleen leucocytes during natural infection with N. melleni suggests that these immune‐related genes play an important role in the initiation of the immune defence mechanism for controlling parasite infection. Interestingly, the magnitude of in vitro responses of spleen leucocytes was dependent on the parasitic stage. An important stimulation of gene expression by adult antigens on spleen leucocytes was observed. Differential expression patterns of TLRs and target cytokines in yellowtail leucocytes in both in vivo and in vitro studies suggest that the quality of yellowtail immune response is conditioned by N. melleni development.

Selective predation by crevalle jack Caranx caninus on engraulid fishes in the SE Gulf of California, Mexico - Cristóbal Sánchez-García; Ofelia Escobar-Sánchez; María Candelaria Valdez-Pineda; Jorge Saúl Ramírez-Pérez; Ramón E. Morán-Angulo; Xchel G. Moreno-Sánchez (Environmental Biology of Fishes, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Olfactory Response and Host Plant Feeding of the Central American Locust Schistocerca piceifrons piceifrons Walker to Common Plants in a Gregarious Zone - M A Poot-Pech; E Ruiz-Sánchez; H S Ballina-Gómez; M M Gamboa-Angulo; A Reyes-Ramírez (Neotropical Entomology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Multimodel ensembles of wheat growth: many models are better than one - Pierre Martre; Daniel Wallach; Senthold Asseng; Frank Ewert; James W. Jones; Reimund P. Rötter; Kenneth J. Boote; Alex C. Ruane; Peter J. Thorburn; Davide Cammarano; Jerry L. Hatfield; Cynthia Rosenzweig; et al. (Global Change Biology, 2015)
Crop models of crop growth are increasingly used to quantify the impact of global changes due to climate or crop management. Therefore, accuracy of simulation results is a major concern. Studies with ensembles of crop models can give valuable information about model accuracy and uncertainty, but such studies are difficult to organize and have only recently begun. We report on the largest ensemble study to date, of 27 wheat models tested in four contrasting locations for their accuracy in simulating multiple crop growth and yield variables. The relative error averaged over models was 24–38% for the different end‐of‐season variables including grain yield ( GY ) and grain protein concentration ( GPC ). There was little relation between error of a model for GY or GPC and error for in‐season variables. Thus, most models did not arrive at accurate simulations of GY and GPC by accurately simulating preceding growth dynamics. Ensemble simulations, taking either the mean (e‐mean) or median (e‐median) of simulated values, gave better estimates than any individual model when all variables were considered. Compared to individual models, e‐median ranked first in simulating measured GY and third in GPC . The error of e‐mean and e‐median declined with an increasing number of ensemble members, with little decrease beyond 10 models. We conclude that multimodel ensembles can be used to create new estimators with improved accuracy and consistency in simulating growth dynamics. We argue that these results are applicable to other crop species, and hypothesize that they apply more generally to ecological system models.

Bactericidal effect of bovine lactoferrin and synthetic peptide lactoferrin chimera in Streptococcus pneumoniae and the decrease in luxS gene expression by lactoferrin - Nidia León-Sicairos; Uriel A. Angulo-Zamudio; Jorge E. Vidal; Cynthia A. López-Torres; Jan G. M. Bolscher; Kamran Nazmi; Ruth Reyes-Cortes; Magda Reyes-López; Mireya de la Garza; Adrian Canizalez-Román (BioMetals, 2014)

Methamphetamine Induces Low Levels of Neurogenesis in Striatal Neuron Subpopulations and Differential Motor Performance - I. K. Tulloch; L. Afanador; L. Baker; D. Ordonez; H. Payne; I. Mexhitaj; E. Olivares; A. Chowdhury; J. A. Angulo (Neurotoxicity Research, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

A deformation/blurring-based spatio-temporal model - J. M. Angulo; A. E. Madrid (Stochastic Environmental Research and Risk Assessment, 2014)

Purification and characterization of a soluble β-1,4-glucan from bean (Phaseolus vulgaris L.)-cultured cells dehabituated to dichlobenil - Ana Alonso-Simón; Antonio E. Encina; Tomoko Seyama; Tetsuo Kondo; Penélope García-Angulo; Jesús M. Álvarez; Jose L. Acebes; Takahisa Hayashi (Planta, 2013)

Entropy-based correlated shrinkage of spatial random processes - J. M. Angulo; A. E. Madrid; M. D. Ruiz-Medina (Stochastic Environmental Research and Risk Assessment, 2011)

Are compound leaves an adaptation to seasonal drought or to rapid growth? Evidence from the Amazon rain forest - Ana C. M. Malhado; Robert J. Whittaker; Yadvinder Malhi; Richard J. Ladle; Hans ter Steege; Oliver Phillips; L. E. O. C. Aragão; Timothy R. Baker; Luzmilla Arroyo; Samuel Almeida; Niro Higuchi; Tim J. Killeen; et al. (Global Ecology and Biogeography, 2010)
Aim To assess the hypotheses that compound leaves of trees in the Amazon forest are an adaptation to drought and/or rapid growth. Location Amazon rain forest, South America. Methods Genera from 137 permanent forest plots spread across Amazonia were classified into those with compound leaves and those with simple leaves. Metrics of compound leaf prevalence were then calculated for each plot and regression models that accounted for spatial autocorrelation were used to identify associations between climate variables and compound leaf structure. We also tested for associations between compound leaf structure and a variety of ecological variables related to life history and growth strategies, including wood density, annual increase in diameter and maximum height. Results One plant family, Fabaceae, accounts for 53% of compound‐leaved individuals in the dataset, and has a geographical distribution strongly centred on north‐east Amazonia. On exclusion of Fabaceae from the analysis we found no significant support for the seasonal drought hypothesis. However, we found evidence supporting the rapid growth hypothesis, with possession of compound leaves being associated with faster diameter growth rates and lower wood densities. Main conclusion This study provides evidence that possession of compound leaves constitutes one of a suite of traits and life‐history strategies that promote rapid growth in rain forest trees. Our findings highlight the importance of carefully considering the geographical distribution of dominant taxa and spatial clustering of data points when inferring ecological causation from environment–trait associations.

Guiding Principles for Small-Scale Forestry in a Watershed of the Venezuelan Andes: Constraints and Opportunities - A. Torres-Lezama; E. Vilanova; H. Ramírez-Angulo (Small-scale Forestry, 2009)

β-Glucuronidase and hexosaminidase are marker enzymes for different compartments of the endo-lysosomal system in mussel digestive cells - U. Izagirre; E. Angulo; S. C. Wade; I. ap Gwynn; I. Marigómez (Cell and Tissue Research, 2009)

Supplementation with bypass fat in silvopastoral systems diminishes the ratio of milk saturated/unsaturated fatty acids - L. Mahecha; J. Angulo; B. Salazar; M. Cerón; J. Gallo; C. H. Molina; E. J. Molina; J. F. Suárez; J. J. Lopera; M. Olivera (Tropical Animal Health and Production, 2008)

Increase in XET activity in bean (Phaseolus vulgaris L.) cells habituated to dichlobenil - A. Alonso-Simón; P. García-Angulo; A. E. Encina; J. M. Álvarez; J. L. Acebes; T. Hayashi (Planta, 2007)

Glycosylation and sorting pathways of lysosomal enzymes in mussel digestive cells - Y. Robledo; I. Marigómez; E. Angulo; M. P. Cajaraville (Cell and Tissue Research, 2006)

First synthesize new viruses then regulate their release? The case of the wild rabbit - E. Angulo; B. Cooke (Molecular Ecology, 2002)
European wild rabbits originated in southwestern Europe but have been introduced into many other countries world‐wide, becoming serious pests in many instances. As a consequence of rabbits being regarded so differently, applied research for their management often has opposing goals, namely their conservation or their control. Furthermore, modern gene technology has led to the concept of using genetically modified myxoma viruses for rabbit management, again with quite contrary aims in mind. In this paper we explain the possible ecological and economic consequences of using these genetically modified viruses inappropriately and we consider whether national and international regulations are sufficient to prevent improper use. If international regulations are inadequate, molecular biologists and ecologists must consider the consequences of their research and advice beyond their own country to avoid unwanted impacts.

Comparison of hydroponic and aeroponic cultivation systems for the production of potato minitubers - E. Ritter; B. Angulo; P. Riga; C. Herrán; J. Relloso; M. San Jose (Potato Research, 2001)

Serologische Untersuchungen zur Prävalenz von Antikörpern gegen aviäres Paramyxovirus der Serotypen 1, 2 und 3 bei frei lebenden Rothühnern(Alectoris rufa) in Südspanien - Ursula Höfle; C. Gortázar; E. Angulo; E. F. Kaleta; R. Villafuerte (European Journal of Wildlife Research, 2001)

Automated measurement of lysosomal structure alterations in oocytes of mussels exposed to petroleum hydrocarbons - Miren P. Cajaraville; J. A. Marigmez; E. Angulo (Archives of Environmental Contamination and Toxicology, 1991)

Ultrastructural alterations in the renal epithelium of cadmium-treatedLittorina littorea (L.) - J. A. Marigmez; M. P. Cajaraville; E. Angulo; J. Moya (Archives of Environmental Contamination and Toxicology, 1990)